Step by step 3D/4D ultrasound in obstetrics, gynecology, and infertility - Singh, Kuldeep (Consultant ultrasonologist); Malhotra, Narendra (Jaypee Brothers Medical Publishers (P) LTD, 2013)
Fully updated, this new edition is a step by step guide to 3D and 4D ultrasound in obstetrics, gynaecology and infertility. Previous edition published in 2008.